2011
DOI: 10.1016/j.vaccine.2011.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of protease ClpP from Streptococcus pneumoniae in Escherichia coli: Study of the influence of kanamycin and IPTG concentration on cell growth, recombinant protein production and plasmid stability

Abstract: Infections caused by Streptococcus pneumoniae are one of the main causes of death around the world. In order to address this problem, investigations are being made into the development of a protein-based vaccine. The aims of this study were to clone and express ClpP, a protein from S. pneumoniae serotype 14 in Escherichia coli, to optimize protein expression by using experimental design and to study plasmid segregation in the system. ClpP was cloned into the pET28b vector and expressed in E. coli BL21 Star (DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 32 publications
2
31
0
2
Order By: Relevance
“…The E. coli from different strains responded differently with IPTG. [32] The previous reports and our study were associated with the importance of IPTG concentration. This parameter incorporated cells density and the recombinant protein yield.…”
Section: Enhanced Production Of Extracellular Single Chain Variable Fsupporting
confidence: 60%
“…The E. coli from different strains responded differently with IPTG. [32] The previous reports and our study were associated with the importance of IPTG concentration. This parameter incorporated cells density and the recombinant protein yield.…”
Section: Enhanced Production Of Extracellular Single Chain Variable Fsupporting
confidence: 60%
“…This phenomenon could be explained by the toxic characteristic of IPTG, which is widely reported in literature [31,37]. Noteworthy, expression of other recombinant proteins from S. pneumoniae studied in our laboratory (PsaA and ClpP protease) , using this same host system, showed a negative effect of IPTG on cell growth [7,31]. …”
Section: Resultsmentioning
confidence: 59%
“…Finally, kanamycin concentration showed no statistical effect on this response, as it happened when it was evaluated in recombinant ClpP protein expression [31]. …”
Section: Resultsmentioning
confidence: 99%
“…Another aspect to be considered is the growth inhibition of these cultures because of the presence of IPTG itself. The addition of inducers is an important variable in the production of proteins, especially on a large scale, since IPTG is costly and it can be toxic to cells (Einsfeldt et al 2011). Pan et al (2008) confirmed that IPTG used to induce expression of cloned genes is a toxic compound that in high concentrations drastically reduces cell growth in some cultures of recombinant E. coli.…”
Section: Resultsmentioning
confidence: 85%